Returning to Capitalism in order to Escape Crises (an excerpt) - Salin, Pascal (Journal of Economic Sociology, 2014)
In the book “Returning to Capitalism in order to Escape Crises” (“Revenir au capitalisme pour éviter les crises”) P. Salin, professor of Economics at University Paris-Douphine, provides his analysis of the 2007–2009 financial crisis with the purpose to develop general conceptualization of financial and economic crises. The author aims to convince the readers that economists have all necessary and reliable theoretical tools to deal with economic crises in the contemporary world. His main argument is that the state interventionism brought out the financial crisis. That’s why a solution should be sought in the proper functioning of markets. Journal of Economic Sociology publishes the book’s “Conclusion. What is ‘moral’?” It discusses a breach of moral principles resulting in crises of capitalistic systems. For better understanding this, Salin considers different types of ethics, discusses issues of morality of capitalism per se, and conceptualizes whether it is adequate to claim that the 2007–2009 financial crisis was rooted into ethical one. In addition, the author concludes that the state interventionism appears to be the main resource for amorality.